Internet of things-based garbage monitoring system integrated with Telegram - Siti Nur Syuhada Ahmad Tarmizi; Nik Nur Shaadah Nik Dzulkefli; Rina Abdullah; Syila Izawana Ismail; Suziana Omar (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This paper presents the development of smart garbage monitoring system usin g internet of things (IoT) to keep the environment clean thus reducing cleaners’ burden. The present era is characterized by smart cities, where precision and organization are the norm. This initiative was launched because population is progressing rapidly, increasing more garbage hence esclating cleaner’s frequency of dustbin checking daily whether the dustbin is full or not which mean more labour costs. The main purpose of this researc h is to develop a systematic garbage monitoring system which can help cleaners schedule their work in monitoring and picking up garbage from dustbins. It used node microcontroller (NodeMCU) ESP8266 Wi - Fi module as the main controller to control ultrasonic and rain input sensors and provide notifications via Telegram. A limit switch is used to detect whether the lid is open or closed. When the lid is closed, the ultrasonic sensor is activated and measures the garbage distance depending on the amount. If an overrun of the maximum amount is detected, the red - light emitting diode (LED) will turn on that connects to the Wi - Fi module, which sends notification to the cleaners. As a result, the IoT based garbage monitoring system was fully functioned and accomplish ed its objectives.